Weed control using no-till soybean growing technology in the Right-Bank Forest-Steppe of Ukraine - Zadorozhnyi, V.; Chernelivska, O.; Labunets , A. (Quarantine and plant protection, 2025)
Goal. To study the effect of long-term application of moldboard tillage (plowing) to a depth of 20—22 cm and no-till technology on weed infestation, and to develop a weed control system to reduce the carbon footprint in soybean cultivation technologies. Methods. The research included field and laboratory studies, as well as mathematical-statistical analysis to assess the reliability of the obtained data. The primary tillage methods were: moldboard plowing to a depth of 20—22 cm and no-till technology. Results. Analysis of the weed species composition in soybean crops, averaged over 2021—2024, revealed 17 species from 10 families. Before the application of post-emergence herbicides, the total number of weeds amounted to 329 plants/m² under moldboard plowing and 367 plants/ m² under no-till technology. Regardless of the primary tillage method, annual dicotyledonous species dominated the weed community (77—88%), with white goosefoot (Chenopodium album L.) prevailing (64—78%) and spotted lady’s thumb (Polygonum persicaria L.) accounting for 8—14%. A significant increase in the number of Canadian fleabane (Erigeron canadensis L.) was observed with long-term no-till application compared to plowing. Application of herbicides with different mechanisms of action—specifically, the graminicide Miura EC (quizalofop-P-ethyl, 125 g/L) at 1.0 L/ha, and a tank mixture of Basagran SL (bentazon, 480 g/L) at 1.8 L/ ha + Harmony WG (thifensulfuron-methyl, 750 g/kg) at 7 g/ ha — reduced total weed infestation by 93% under moldboard plowing and by 95% under no-till technology. Grass weed control reached 96—97%, while the mixture of Basagran SL 1.8 L/ ha + Harmony WG 7 g/ha ensured 93—98% mortality of dicotyledonous species. Under no-till technology, the use of the non-selective herbicide Roundup Max SL (450 g/L glyphosate acid equivalent; 551 g/L as potassium salt) at 2.5 L/ha, applied 10 days before sowing, ensured E. canadensis control at the level of 90%, which may require additional measures in the future. Average soybean yield under moldboard plowing was 3.1 t/ha, while under no-till with effective weed control it was 2.84 t/ha. Production costs for soybean cultivation under no-till were 23.5 thousand UAH/ ha, compared to 26.7 thousand UAH/ ha under plowing — 3.2 thousand UAH/ ha lower. Fuel and lubricants consumption was reduced by 22—25 L/ha, and profitability increased to 86%, which is 15% higher than under plowing. Conclusions. The weed control system, which includes the application under no-till technology of the non-selective herbicide Roundup Max SL at 2.5 L/ha 10 days before sowing, the graminicide Miura EC at 1.0 L/ ha, and the tank mixture of Basagran SL 1.8 L/ha + Harmony WG 7 g/ha at the 1—3 trifoliate leaf stage of the crop during the juvenile stages of weed development, is a key element in low-carbon soybean cultivation technology.